Studies on the Credibility of Wikipedia: A Review - Claes, Florencia; Tramullas, Jesús (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2021)
The evaluation of the credibility of Wikipedia has received special attention in studies on the credibility of information on the web. This paper presents a state of the art, which has been carried out following the systematized literature review technique. Three types of studies have been differentiated: general studies, the health field and the educational field. The data support the conclusion that different models and analysis techniques for such studies are applied; that the heuristic principles of user evaluation play a key role; and that assessments of credibility are influenced by user’s social and educational contexts, and by the type of information needed. Finally, it is stated that credibility is part of a continuous process of change and interaction.
Keywords: Credibility; Wikipedia; Heuristic Process; Information Behavior